Multimodal imaging in the diagnosis and management of ophthalmia nodosa - Noy Ashkenazy; Philip J. Rosenfeld; Janet L. Davis (American Journal of Ophthalmology Case Reports, 2022)
Purpose: Ophthalmia nodosa (ON) is a rare but important disease describing ocular inflammation caused by injury from insect hairs (“setae”). Type V ON occurs when there is vitreoretinal involvement. Treatment with systemic steroids are first-line, but vitrectomy is indicated in resistant cases. The purpose of this study was to illustrate how multimodal imaging can facilitate diagnosis and management of ON. Observations: This is a single retrospective case report of a patient who presented to Bascom Palmer Eye Institute with Type V ON. Multimodal imaging in a patient with Type V ON was illustrated. A moth seta was localized to the anterior vitreous cavity. Intraocular inflammation responded to 2 weeks of high-dose oral prednisone. Conclusions and Importance: Multimodal imaging may guide diagnosis and management of ON by documenting baseline features of ON and facilitating comparison at follow up visits. This allows for safe non-surgical management of Type V ON. Long-term follow up would be necessary to determine whether subsequent surgical intervention was needed in this case.